2019
DOI: 10.9734/afsj/2019/v11i130054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation on Antinutritional Factors and Functional Properties of Fermented Bambara Nut Flour

Abstract: Bambara nut (Vigna subterrenean) is a cheap source of leguminous protein that can be a good substitute for relatively expensive animal protein to reduce malnutrition. Despite its potentials, it remains underutilized owing in part to long cooking time, presence of antinutritional factors and drudgery in dehulling. In this regard, this study determined effects of fermentation on antinutritional and functional properties of bambara nut flour. Bambara nut was procured from local market in Abeokuta while pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A number of studies have reported reductions in oxalate concentrations after fermentation-27% in dawadawa [142], 62-77% in ugba [173], 36-52% in fermented Bambara groundnut flour [176], 67% in fermented horse gram flour [183] and 95% in fermented lima bean [186], with such reductions attributed to the utilization of oxalate as a carbon source of microbes and the microbial degradation of ANF-related components [183,186]. It has also been suggested that the reduction in oxalate content following fermentation can be attributed to the hydrolytic action of enzymes produced during fermentation [213].…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…A number of studies have reported reductions in oxalate concentrations after fermentation-27% in dawadawa [142], 62-77% in ugba [173], 36-52% in fermented Bambara groundnut flour [176], 67% in fermented horse gram flour [183] and 95% in fermented lima bean [186], with such reductions attributed to the utilization of oxalate as a carbon source of microbes and the microbial degradation of ANF-related components [183,186]. It has also been suggested that the reduction in oxalate content following fermentation can be attributed to the hydrolytic action of enzymes produced during fermentation [213].…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…Several studies have shown that fermentation reduces the phytate content of BG by 18.1 -95.9% Ijarotimi and Esho 2009;Ogodo et al 2018a;Ola and Opaleye 2019;Olanipekun, Otunola, and Oyelade 2015;Pahane et al 2017) (Table 4). A reduction in phytate content could be due to the activation of phytase and phosphophytase enzymes, which are either naturally occurring in the BG or synthesized by the fermenting microorganisms and subsequently hydrolyze phytate into lower esters (e.g., IP5, IP4), thereby releasing phosphorus as well as any phytate-bound nutrients Ola and Opaleye 2019;Olanipekun, Otunola, and Oyelade 2015). In addition, the lactic acid produced during LAB fermentation leads to a rapid decrease in pH, favoring phytase stability and activity (Castro-Alba et al 2019;Ogodo et al 2018a).…”
Section: Phytatementioning
confidence: 96%
“…Several studies suggested that fermentation can effectively decrease the tannin content of BG from 25.6 to 98.3% Ijarotimi and Esho 2009;Ogodo et al 2018a;Ola and Opaleye 2019;Olanipekun, Otunola, and Oyelade 2015) (Table 5). The reduction in tannin content is likely due to the action of tannase or polyphenol oxidase (PPO) enzymes that are either present in the legume or are secreted by the fermenting microorganisms.…”
Section: Tanninsmentioning
confidence: 99%
See 2 more Smart Citations